Effects of antireflective coatings on scanning performance of millimetre-wave lenses - Sonmez, Nurdan T.; Tokan, Nurhan T. (INST ENGINEERING TECHNOLOGY-IET, 2016)
This study examines the beam scanning performance of the antireflective coatings designed on millimetre-wave integrated lens antennas with dense material. Dielectric lens antennas fabricated with a dense dielectric material allow good power transfer efficiency through the lens and enable fabrication of low-cost and compact-size lens antennas. However, using dense dielectric material causes strong multiple internal reflection behaviour inside the lens antenna. These multiple reflections deteriorate not only the return loss but also the radiation characteristics. Wide angle scanning performance is limited due to off-axis aberrations. Effects of strong internal reflections can be reduced considerably using one or more dielectric matching layers coated at the top of the antenna. A 77 GHz extended hemispherical lens antenna made of alumina is coated with different types of solutions for antireflection layers, namely, conventional quarter-wave transformer, multiple layer transformer, linear and circular corrugations and their performance in beam scanning applications is observed. The lens is illuminated by an aperture coupled microstrip antenna designed to radiate into alumina at 77 GHz. A frequency-dependent characterisation of the beam pattern clearly showed the existence and impact of internal reflections on beam scanning performance for 77 GHz automotive radar antennas.
Keywords: ANTENNAS; BAND; SILICON; DESIGN; Engineering; Telecommunications